(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article discusses the advantages of such methods, such as active participation in the learning process, development of critical thinking, motivation and social skills. Strategies for effectively using interactive methods in teaching are also described.